Approaching to biogenic amines as quality markers in packaged chicken meat - Esposito, Luigi; Mastrocola, Dino; Martuscelli, Maria (Frontiers in Nutrition, 2022)
Following the chicken meat quality decay remains a tricky procedure. On one hand, food companies need of fast and affordable methods to keep constant higher sensory and safety standards, on the other hand, food scientists and operators find difficult conjugating these exigencies by means of univocal parameters. Food quality definition itself is, in fact, a multi-layered and composite concept in which many features play a part. Thus, here we propose an index that relies on biogenic amines (BAs) evolution. These compounds may indirectly inform about microbial contamination and wrong management, production, and storage conditions of meat and meat products. In this study, three cuts of chicken meat (breast fillets, drumsticks, and legs) packaged under modified atmosphere, under vacuum, and in air-packaging, and stored at +4°C (until to 15 days),were analysed. Some BAs were combined in an index (BAI) and their evolution was followed. The Thiobarbituric Acid Reactive Species assay (TBARS) was also used as a common reference method. Generally, BAI may better identify the beginning of quality impairment than lipid oxidation spreading. ANOVA statistical analysis has highlighted that the storage time is anyway the most detrimental factor for chicken decay when it is stored in refrigerated rooms (P> 0.01). Despite TBARS still remains a powerful tool for chicken goods, its exclusive use may not be enough to explain quality loss. On the contrary, BAI implementation in fresh meat can give a more complete information combining food safety exigencies with sensory attributes.